Aging, Pension System, and Economic Growth in Poland and Thailand - Prapaipanich, Nattaya; Golota, Lukasz; Ratniyom, Aotip; Saleepon, Ravipan; Srisaringkarn, Thanakhom; Sukpaiboonwat , Sivalap (Journal of Multidisciplinary in Social Sciences, 2025)
This research aimed to analyze the situation of aging, the pension system, and economic growth. There were two objectives using qualitative and quantitative methodology. The first objective aimed to analyze the situation of aging and the pension system in Poland and Thailand by using comparative analysis. The study found that Poland's pension system ensures that the majority of the population receives retirement benefits by offering rather comprehensive coverage. However, in Thailand, only those who work in the formal sector are covered by Thailand's social security system. It implies that a significant proportion of the population, particularly those in the informal sector and those living in rural areas, does not have enough pension coverage. This makes it challenging to ensure financial stability as one ages. The second objective was to examine the relationship between retirement savings and economic growth in Thailand by using OLS regression. This research used time series data and applied quarterly data from Q1 2007 to Q4 2020. The regression results revealed that five variables had a statistically significant effect on economic growth in Thailand, which were Social Security Fund Article 33 (SSF33), Private Investment (I), Retirement Mutual Fund (RMF), Government Spending (G), and Government Pension Fund (GPF). The results confirm that retirement savings are important to the economy’s growth. This research also highlights the important role of pension systems in addressing the challenges of aging populations. A well-planned pension system provides financial security for retirees and supports economic growth. By comparing Poland and Thailand, this study provides valuable understanding for creating sustainable pension systems that can adapt to population changes and strengthen the economy.